Scoping Review: Intervensi WASH pada Daerah Bencana Banjir dan Dampaknya Terhadap Penyakit Menular - Rika Nurfadhilah; Suherman Jaksa; Triana Srisantyorini (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Background: Floods are the most frequently occurring natural disasters globally and have the potential to trigger massive outbreaks of infectious diseases. Disruption to clean water and sanitation infrastructure places communities at high risk for waterborne, vector-borne, and environmentally-transmitted diseases. Water, Sanitation, and Hygiene (WASH) interventions are believed to play a central role in breaking the chain of disease transmission post-flood, yet scientific evidence comprehensively summarizing the effectiveness of these interventions in flood disaster contexts remains limited. Objective: To map scientific evidence on the type, scope, and effectiveness of WASH interventions in flood disaster areas and their impact on the incidence of infectious and vector-borne diseases. Methods: A scoping review methodology was employed, with relevant articles identified through a systematic search of national and international databases including Google Scholar, PubMed, and Science Direct. Inclusion criteria covered empirical studies analyzed narratively, published between 2016–2026. Results: The most commonly reported WASH interventions include provision of safe drinking water (chlorination, filtration), emergency sanitation, handwashing promotion, and hygiene kit distribution. These interventions were consistently associated with a reduction in diarrhea incidence rates (30–50%). Intervention effectiveness was influenced by speed of response, community involvement, and logistics availability. Conclusion: WASH interventions have proven effective in reducing the burden of infectious disease during flood disasters. Standardization of WASH intervention protocols in disaster response is needed, along with strengthening local capacity for rapid and targeted implementation.